Analysis of Qr Code Technology Acceptance in Cocoa Production Forecasting Based on Motivation, Farmer Characteristics, and Innovation Nature - Ramdan Ramdan; Iwan Setiawan; Anne Charina (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
QR Code technology is used to help record cocoa production forecasts efficiently and accurately, so that farmers can easily update data in real-time. However, in its application, farmers still record production forecasts manually, which often results in discrepancies between forecasts and actual results and takes a long time in the process. This study aims to analyze QR Code technology acceptance among farmers assisted by PT X in the process of forecasting cocoa production in terms of the influence of motivation, farmer characteristics, and the nature of the innovation contained in the technology. This study used a quantitative verification method, supported by the SEM-PLS analysis tool. Samples were taken using a census method from 108 cocoa farmers assisted by PT X in Bulungan Regency. The results of the study showed that motivation, farmer characteristics, and the nature of innovation have a direct, positive and significant effect on QR code technology acceptance. Furthermore, QR Code technology acceptance is positively and significantly influenced by farmer characteristics through motivation as a mediating variable. However, the nature of innovation does not have a positive and significant effect on QR Code technology acceptance through motivation, and the nature of innovation also does not have a direct, positive and significant effect on motivation. These findings confirm that farmer motivation and characteristics need to be improved to increase QR Code technology acceptance. This will enable production forecasting to generate accurate data to inform cocoa production decisions and ensure the availability of cocoa bean raw materials for processors.